Investigation of Pressure Signal and Leak Detection in Pipes by Using Wavelet Transform in Transient Flow - Nasim Vafaei Rad; Hossein Azizi Nadian; Roberto Ranzi; Mostafa Rahmanshahi; Mahmood Shafaei Bejestan (Engineering Proceedings)
Leakages in pipes lead to water loss, so leak detection to prevent water loss is essential. Transient flow is a method to obtain a wide range of pipe flow data, but generally, signal data have various noises also related to leakages. One effective way to detect leaks is to use wavelet transform (WT). So, in this study, by conducting laboratory experiments and using WT, the behavior of the signal and the effectiveness of wavelet transform were investigated. Results of the research showed that WT is very effective for leak detection, noise reduction, and signal analysis for transient flow.